The bayesian approach of factors associated with preterm birth among mothers delivered at public hospitals in Southeast Ethiopia - Negesse, Yilkal; Abebe, Gossa Fetene (Frontiers in Public Health, 2023)
Background: Preterm birth remains the commonest cause of neonatal mortality, and morbidity representing one of the principal targets of neonatal health care. Ethiopia is one of the countries which shoulder the highest-burden of preterm birth. Therefore, this study was aimed to assess factors associated with preterm birth at public hospitals in Sidama regional state. Methods: Facility based cross-sectional study was conducted at public hospitals in south east Ethiopia, from 1st June to 1st September/2020. To recruit the study participants, systematic random sampling techniques were used. Data were collected using pretested structured interviewer-administered questionnaire, and checklist via chart review. Data were entered using Epi-data version 3.1 and exported to R software version 4.0 for analysis. Then factors associated with preterm birth among mothers was assessed based on Bayesian statistical approach. Results: The study showed that the prevalence of preterm birth was 20.6%. Being rural resident (AOR=2; 95% CrI 1.2-3.5), no antenatal care service utilization (AOR=2.3; 95% CrI 1.1- 4.8), hypertensive disorder of pregnancy (AOR=3.5; 95% CrI 1.8- 6.9), birth space less than 2 years (AOR=3.4; 95% CrI 1.5-7.9), having premature rupture of membrane (AOR=2.4; 95% CrI 1.3- 5.4) and physical intimate violence (AOR=2.876; 95%CI: 1.534, 5.393) were risk factors of preterm birth. Whereas, women who had primary, secondary and higher education level (AOR=0.2; 95% CrI 0.1-0.4, AOR=0.1; 95% CrI 0.06-0.3, and AOR=0.2; 95% CrI 0.1-0.4) respectively were preventive factor. Conclusion: Most of the risk factors of preterm birth were found to be modifiable. Community mobilization on physical violence during pregnancy and antenatal care follow-up are the ground for the prevention of preterm birth because attentive and critical antenatal care screening practice could early identify risk factors. Besides, information communication education about preterm birth prevention was recommended.